Insights from genomes and genetic epidemiology of SARS-CoV-2 isolates from the state of Andhra Pradesh. (3rd August 2021) - Roja Rani, Pallavali; Imran, Mohamed; Lakshmi, J. Vijaya; Jolly, Bani; Afsar, S.; Jain, Abhinav; Divakar, Mohit Kumar; Suresh, Panyam; Sharma, Disha; Rajesh, Nambi; Bhoyar, Rahul C.; Ankaiah, Dasari; et al.
Abstract: Coronavirus disease 2019 (COVID-19) emerged from a city in China and has now spread as a global pandemic affecting millions of individuals. The causative agent, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is being extensively studied in terms of its genetic epidemiology using genomic approaches. Andhra Pradesh is one of the major states of India with the third-largest number of COVID-19 cases with a limited understanding of its genetic epidemiology. In this study, we have sequenced 293 SARS-CoV-2 genome isolates from Andhra Pradesh with a mean coverage of 13324X. We identified 564 high-quality SARS-CoV-2 variants. A total of 18 variants mapped to reverse transcription polymerase chain reaction primer/probe sites, and four variants are known to be associated with an increase in infectivity. Phylogenetic analysis of the genomes revealed the circulating SARS-CoV-2 in Andhra Pradesh majorly clustered under the clade A2a (20A, 20B and 20C) (94%), whereas 6% fall under the I/A3i clade, a clade previously defined to be present in large numbers in India. To the best of our knowledge, this is the most comprehensive genetic epidemiological analysis performed for the state of Andhra Pradesh.